Bonsai : in cooperation with the Brooklyn Botanic Garden - Resnick, Susan M. Bachenheimer; Brooklyn Botanic Garden (Surrey : Bramley Books, 1998)
Discusses the history and tradition of bonsai, and explains how to buy, grow, style, shape, prune, and display them
Includes index.
Keywords: Bonsai -- Handbooks, manuals, etc; Bonsaï -- Guides, manuels, etc